Occasional and consistent swing voters: Two types of swing voters - Shamshiri-Petersen, Ditte (Politica, 2018)
The share of swing voters in Danish general elections has increased substantially over the past decades. Today, more than one-third of Danish voters switch party between national elections. Most literature peg swing voters as less politically engaged and competent. However, swing voters are not a homogeneous group. Analysis of panel survey data from 2001-2005 reveals significant differences between occasional and consistent swing voters. Whereas voters who switch party time after time indeed tend to be less engaged and knowledgeable about politics, this does not apply to voters who switch only occasionally.